Les mots croisés de Détective, ou l’Œdipe sans complexe - Paul Aron (Criminocorpus)
For a few weeks, in the first issues of the the review Detective, there appeared crosswords in the form of handcuffs, criminal mask or weapons. What is the reason for this publication, and how can it be explained that it stops after 8 grids? To answer these questions, it is necessary to take up the history of this game, and to show its French and literary sources. The article traces the progressive elaboration of modern crosswords in the long history of the graphic enigma in the press. A « space of possibilities » emerges from there, which permits to understand the form of the grids of Detective and the reasons for their rapid disappearance.